Algas no planctónicas: un experimento de colonización - Esquiús, K. S. (2006)
The aim of the present research is to study the algal colonization process using artificial substrata placed in Los Padres Lagoon waters (Province of Buenos Aires) during summer. The area selected for sampling were the influent stream (Los Padres Creek) and the effluent (La Tapera Creek) due to the large amount of «giant bulrush» Schoenoplectus californicus found there. In each area two samplers containing ten slides arranged in two columns were vertically placed. The first removal was carried out after a week, the second one after two days and third one after four days. The fourth and fifth removals were carried out following a geometric progression during 37 days of colonization. Colonizing community was removed from the substrata by scraping their surfaces. Ninety nine epiphytic algae species were identified. Among them, diatoms represented the dominant group. The number of algae species and their abundance were higher in the output area (La Tapera Creek), while the specific diversity was higher in the input area (Los Padres Creek). The longer exposition period artificial substrata had, the higher algae species number developed. The exposition period employed allowed to observe the maturity of the epiphyton community, and the decrease of algal density after 13 and 21 days of colonization in the input and output areas, respectively. It was concluded that an exposition period of about a month results appropriate for the attached algae to reach the complete colonization of artificial substrata in a moderately eutrophic lagoon.